An Inter‐ and Intraprofessional Education Program in Which Dental Hygiene Students Instruct Medical and Dental Students. Issue 9 (1st September 2016) - Otsuka, Hiromi; Kondo, Keiko; Ohara, Yuki; Yasuda, Masayo; Kishimoto, Natsuki; Sunaga, Masayo; Endo, Keiko; Arakawa, Shinichi; Kinoshita, Atsuhiro; Shinada, Kayoko
Abstract : The aim of this study was to develop, implement, and evaluate an inter‐ and intraprofessional education program with a peer support joint practice in which dental hygiene students teach medical and dental students about oral health care for older people requiring long‐term care. In 2015 at Tokyo Medical and Dental University, 22 dental hygiene students in their third year at the School of Oral Health Care Sciences (OH3), 110 students in their third year at the School of Medicine (M3), and 52 students in their third year at the School of Dentistry (D3) participated in this program. The OH3 students practiced with a whole‐body‐type simulator to learn oral health care for older people and then taught the methods to the M3 and D3 students according to their self‐designed teaching plan. All M3 and D3 students experienced being both practitioner and patient. The number of respondents and response rates on the questionnaires after the training were 22 (100%), 102 (92.7%), and 52 (100%) for the OH3, M3, and D3 students, respectively. Self‐assessment by the OH3 students indicated that they could supervise other students sufficiently (77–86%), and 91% of them found the preclinical practice with the simulator efficient for the peer support joint practice. Almost all the M3 and D3 students reported that they gained understanding of the methods (99%), significance (100%), and important points of oral health care for older people (97%) in addition to the jobs and roles of dental hygienists (93%) because of this program. The M3 students understood the methods and significance of oral health care more deeply than did the D3 students (p<0.05). This study found that an interprofessional program with a peer support joint practice to cultivate practical clinical ability aided in increasing understanding and cooperation between medicine and dentistry.